Prognostic factors associated with visual field recovery in non-arteritic anterior ischemic optic neuropathy - Heejin Yoon; Su-jin Kim; Seung Min Lee; Sangwoo Moon; JungHyo Ahn; Jae Hwan Choi; Ji Eun Lee (PLoS ONE, 2026)
This study aimed to identify baseline prognostic factors associated with visual field (VF) recovery in patients with non-arteritic anterior ischemic optic neuropathy (NAION). This retrospective study included 38 patients (41 eyes) diagnosed with NAION. VF recovery was defined as an improvement of ≥3 dB in mean deviation (MD) at 3 months. Baseline demographic characteristics, systemic vascular risk factors, visual function tests, and retinal nerve fiber layer (RNFL) thickness measured by optical coherence tomography (OCT) were analyzed. Eleven eyes (26.8%) were classified as the recovery group. Compared with the non-recovery group, the recovery group had significantly better baseline best-corrected visual acuity (BCVA) (P = 0.034) and lower glycated hemoglobin levels (P = 0.033). Baseline VF impairment was significantly less severe in the recovery group, with higher MD (P = 0.049) and visual field index (VFI) values (P = 0.014). No significant association was observed between topical eye drop treatment, including brimonidine and netarsudil, and visual field recovery (p = 0.723). Baseline BCVA strongly correlated with BCVA at 1, 3, and 6 months (all P < 0.001). Multivariate analysis confirmed that better baseline MD (P = 0.041) and higher VFI (P = 0.036) were independently associated with VF recovery. However, RNFL thickness measured at initial visit by OCT did not reliably predict recovery. These findings highlight that baseline functional status remain as the most important predictor of visual field recovery in NAION.